Nacionalismos, identidades y narraciones (2016)
From a critical perspective, in this article different interpretations of the concept of nation are analyzed, highlighting the dangers of its radical defense; then it gives way to the understanding of nationalism from a postmodern approach, which will be a guide to understand new ways of conceiving nationalistic identity projects in Colombia.